Garlic consumption can reduce the risk of dyslipidemia: a meta-analysis of randomized controlled trials - Yanbin Du; Hua Zhou; Wenting Zha (Journal of Health, Population and Nutrition, 2024)
Abstract Background and purpose Garlic is used as an important medicinal food for treatment of many diseases, however, the association between garlic consumption and dyslipidemia have yielded inconsistent results. So we carried this meta-analysis to explore the blood lipid-lowering effects of garlic. Methods Databases such as PubMed, Scopus, Web of science, Embase, Cochrane Library were systematically searched until June 2024. Heterogeneity among studies was examined using Q and I2 statistics. Also subgroup analysis were conducted to explore the potential heterogeneity. Combined weighted mean differences (WMD) with their 95% confidence interval (CI) were calculated using a random-effects model. The GRADE approach was used to evaluate the overall certainty of the evidence in the meta-analyses. Results A total of 21 RCTs studies involved association between garlic consumption and blood lipids level of dyslipidemia patients were included in the meta-analysis. The pooled results showed that garlic consumption significantly reduced total cholesterol (TC)(WMD = -0.64mmol/L, 95%CI = -0.75 −-0.54, P < 0.001), triglyceride (TG)(WMD = -0.17mmol/L, 95%CI = -0.26 −-0.09, P < 0.001), low-density lipoprotein(LDL-C)(WMD = -0.44mmol/L, 95%CI = -0.57 −-0.31, P < 0.001) while slightly increased high-density lipoprotein (HDL-C)(WMD = 0.04mmol/L, 95%CI = -0.00 − 0.08, P < 0.001). And subgroup analyses showed that TC, TG and LDL-C significantly decreased in patients aged > 50 years compared to those aged ≤ 50 years. And garlic oil greatly reduced TC and LDL-C compared with garlic power. Finally, sensitivity analysis and publication bias showed that the results were reliable. Conclusions Evidence from this meta-analysis suggested that garlic consumption could be effective in reducing the risk of dyslipidemia and preventing CVDs. Particularly the older people were more susceptible to the protective effects of garlic.